The art of French piano music Debussy, Ravel, Fauré, Chabrier - Howat, Roy 1951- (Yale Univ. Press, 2009)
An essential resource for scholars and performers, this study by a world-renowned specialist illuminates the piano music of four major French composers, in comparative and reciprocal context.